Everyday transgressions : domestic workers' transnational challenge to international labor law - Blackett, Adelle, 1967- (ILR Press, an imprint of Cornell University Press, 2019)
"This book theorizes the law of the household workplace, and how ongoing multilevel regulatory innovation regarding domestic work can be fostered"--